2005
DOI: 10.1002/polb.20416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reactive compatibilization on the properties of poly(butylene terephthalate)/acrylonitrile–ethylene–propylene–diene–styrene blends

Abstract: Blends of poly(butylene terephthalate) (PBT) with 30 wt % acrylonitrile–ethylene–propylene–diene–styrene (AES) were prepared with methyl methacrylate (MMA)/glycidyl methacrylate (GMA)/ethyl acrylate (EA) terpolymers (MGEs) as compatibilizing agents. These acrylic terpolymers were miscible with the styrene–acrylonitrile (SAN) phase of AES, whereas the epoxide groups of GMA could react with the PBT end groups; this could lead to the formation of grafted copolymers (PBT‐g‐MGE) at the PBT/AES interface during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 53 publications
0
24
0
2
Order By: Relevance
“…6 The polymerization reaction was carried out in a reactor under intensive mixing and nitrogen atmosphere at 80 C for 8 h. The copolymers were synthesized with 1, 5, and 10 wt % of MA, using toluene as solvent. To control the molecular weight of the copolymers, the initiator benzoil peroxide was used at different concentrations as follows: for high-molecular-weight (HMW) 1% of peroxide; for medium-molecular-weight (MMW) 2% of peroxide; and for low-molecular-weight (LMW) 5% of peroxide.…”
Section: Synthesis Of the Compatibilizermentioning
confidence: 99%
See 1 more Smart Citation
“…6 The polymerization reaction was carried out in a reactor under intensive mixing and nitrogen atmosphere at 80 C for 8 h. The copolymers were synthesized with 1, 5, and 10 wt % of MA, using toluene as solvent. To control the molecular weight of the copolymers, the initiator benzoil peroxide was used at different concentrations as follows: for high-molecular-weight (HMW) 1% of peroxide; for medium-molecular-weight (MMW) 2% of peroxide; and for low-molecular-weight (LMW) 5% of peroxide.…”
Section: Synthesis Of the Compatibilizermentioning
confidence: 99%
“…Thus, it is necessary to understand the effects of molecular parameters of these copolymers on their ability for compatibilizing the polymer system under study. Larocca et al 6 have observed the compatibilization effects of methyl methacrylate-glycidyl methacrylate (MGE) copolymer on the PBT/AES/MGE blends, where low-molecular-weight MGE grades are more efficient.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of ABS and AES make the ultimate viscosity of PBT/ABS and PBT/ AES blends very high, which causes difficulties in the injection molding step of these systems. Compatibilized PBT/ABS 19,[21][22][23][24][25] and PBT/AES blends, 26 i.e., blends with improved impact properties and more stable phase morphology within a large processing range were obtained using poly (methyl-methacrylateran-glycidyl methacrylate) (MMA-GMA) reactive copolymers as in situ compatibilizers. For PBT/SBS blends, however, compatibilization has still not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizando reometria de torque, Mantovani [5] verificou que ocorreu aumento acentuado do torque quando o MGE foi adicionado à blenda PBT/ABS, e ilustrou a reação de compatibilização da blenda PBT/ABS/MGE. A partir de então foram realizadas diversas pesquisas [6][7][8][9][10][11] com a blenda PBT/ABS compatibilizada com o terpolímero MGE, porém as variáveis de processamento investigadas se restringiram à comparação entre extrusoras com rosca simples e dupla, e perfil térmico na extrusão e na moldagem por injeção. Mais recentemente foram realizadas pesquisas para verificar a influência das condições de processamento em extrusora com rosca dupla corotacional e interpenetrante (ERDCI), sobre as características da blenda PBT/ABS [12] , cujos resultados serão em parte apresentados neste estudo.…”
Section: Introductionunclassified